Wykorzystanie cnót w działalności dydaktyczno-wychowawczej nauczyciela akademickiego - Polok, Grzegorz; Kapias, Michał (Annales. Etyka w Życiu Gospodarczym, 2011)
Prestige of academic teacher’s activities and his or her authority, should most of all result from moral attitude. Thus there is need in this kind of activity to use ethic virtues. Thanks to them human improves internally, but also can realize the concrete property outside. Virtues are necessary for person both for him or her as an average human being and also as a scholar and an educator. By setting own example one can have the most influence on students’ moral attitudes. Consequently an occasion arises to improve cardinal classic virtues, which include: prudence, deliberation, justice and courage, but also in the virtues that are related to them. These activities drive to form yourself in giving good example and have a huge impact on academic environment’s advancement.